Serrated tubulovillous adenoma of the large intestine. Issue 4 (17th September 2015) - Bettington, Mark; Walker, Neal; Rosty, Christophe; Brown, Ian; Clouston, Andrew; McKeone, Diane; Pearson, Sally‐Ann; Klein, Kerenaftali; Leggett, Barbara; Whitehall, Vicki
Abstract : Aims: Most colorectal polyps are classified readily, but a subset of tubulovillous adenomas (TVA) with prominent serrated architecture causes diagnostic confusion. We aimed to (i) identify histological features that separate serrated TVAs from both conventional TVAs and traditional serrated adenomas (TSA) and (ii) perform a clinicopathological and molecular analysis to determine if the serrated TVA has unique features. Methods and results: We collected 48 serrated TVAs, 50 conventional TVAs and 66 BRAF wild‐type TSAs for analysis. For each polyp we performed a clinicopathological assessment, BRAF and KRAS mutation profiling, cytosine–phosphate–guanosine (CpG) island methylator phenotype status, MGMT methylation and immunohistochemical assessment of seven markers [MutL homologue 1 (MLH1), p16, p53, β‐catenin, Ki67, CK7 and CK20]. We found that serrated TVAs can be diagnosed reliably, and have features distinct from both conventional TVAs and TSAs. Compared to conventional TVAs, serrated TVAs are larger, more often proximal, more histologically advanced, show more CpG island methylation and more frequent KRAS mutation. Compared to TSAs they are more often proximal, show less CpG island methylation, more frequent MGMT methylation and more frequent nuclear staining for β‐catenin. Conclusions: The serrated TVA can be diagnosed reliably and has unique features. It represents a precursor of KRAS mutated, microsatellite stable colorectal carcinoma.